Anti-oxidation soldering tin bar and preparation method thereof

By using Sn-Ag-Cu alloy in solder strips with Bi, Ge, P and Sn-Be-Sb ternary alloys, the problems of insufficient spreading coefficient, oxidation resistance and tensile properties of traditional solder strips are solved, and efficient solder strips are achieved and product reliability is improved.

CN119635077AActive Publication Date: 2025-03-18FOSHAN NANHAI DISTRICT SONGGANG HONGYANG STANNUM IND
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411958706.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

During the welding process, traditional solder strips have problems such as poor spreading coefficient, poor oxidation resistance and insufficient tensile performance, resulting in poor mechanical strength and electrical connection stability of the solder joints, and prone to false welding, missing welding and oxidation reactions, affecting the reliability and stability of the product.

Method used

The combination of Sn-Ag-Cu alloy with Bi, Ge, P and Sn-Be-Sb ternary alloy is used to improve the oxidation resistance, spreadability and tensile strength of the solder strip through specific ratios and preparation methods.

Benefits of technology

The solder strips have excellent fluidity, good spreading properties, good low-temperature welding effect and high tensile strength, which reduces the formation of oxide layers, maintains the finish and aesthetics of the welded joints, and improves the welding quality and product reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216550080000051
    Figure BDA0005216550080000051
  • Figure BDA0005216550080000061
    Figure BDA0005216550080000061
Patent Text Reader

Abstract

The invention discloses an anti-oxidation soldering tin bar and a preparation method thereof, and relates to the field of soldering tin materials. The anti-oxidation soldering tin bar comprises Sn-Ag-Cu alloy, Bi, Ge, P and Sn-Be-Sb ternary alloy, and in the Sn-Ag-Cu alloy, the weight ratio of Sn is 96.5%-98.5%, the weight ratio of Ag is 1%-1.5%, and the weight ratio of copper is 0.5%-2%; the doping amount of Bi is 0.01%-0.05% of the Sn-Ag-Cu alloy, the doping amount of Ge is 0.01%-0.06% of the Sn-Ag-Cu alloy, the doping amount of P is 0.05%-0.1% of the Sn-Ag-Cu alloy, the doping amount of Sn-Be-Sb ternary alloy is 1.2%-1.8% of the Sn-Ag-Cu alloy, and in the Sn-Be-Sb ternary alloy, the weight percentage of Be is 4.8%-5.6%, the weight percentage of Sb is 2.5%-3.8%, and the balance is Sn. The anti-oxidation soldering tin bar has the advantages of being good in oxidation resistance, good in spreadability and high in tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solder materials, and in particular to an anti-oxidation solder bar and a preparation method thereof. Background Art

[0002] In many fields such as electronic manufacturing and precision instrument assembly, welding process is the key link to achieve component connection, and the performance of solder bar as the core material in the welding process is directly related to the quality and reliability of the product. With the continuous advancement of science and technology, the demand for miniaturization and high performance of electronic products is increasing, which puts more and more stringent requirements on welding quality.

[0003] Traditional solder bars have gradually exposed many problems in actual use. On the one hand, its spreading coefficient is not ideal, which makes it difficult for the solder to evenly cover the welding surface during the welding process, and it is easy to have defects such as cold welding and leaking welding, which greatly affects the mechanical strength and electrical connection stability of the solder joint. For example, in the welding scenarios of some microelectronic components, due to uneven spreading, tiny solder joints cannot form a good alloy layer. In subsequent use, if they are slightly impacted by external force or temperature changes, the solder joints may crack and fail.

[0004] On the other hand, poor anti-oxidation performance is another shortcoming of traditional solder bars. Under high-temperature welding conditions, solder easily reacts with oxygen in the air to form an oxide film. This not only hinders the good fusion between solder and weldment, reduces welding quality, but also causes solder waste and increases production costs. Moreover, oxidized solder residue adheres to the solder joints and is difficult to clean. If it remains inside electronic products, it may cause short circuits and other hidden faults, seriously affecting the long-term reliability and stability of the product.

[0005] Furthermore, insufficient tensile properties make solder joints prone to breakage when subjected to mechanical stress. This is especially true in connection parts of electronic devices that require frequent plugging and unplugging, vibration, or certain external forces, such as computer motherboard interfaces and mobile phone charging interfaces. If the solder has poor tensile properties and a short fatigue life of solder joints, after a period of use, the solder joints at the interfaces will break, resulting in connection failure, which will directly affect the normal use of the equipment.

[0006] In view of the above-mentioned defects of traditional solder bars, the industry is in urgent need of a solder bar that can effectively solve the problems of spreading coefficient, anti-oxidation performance and tensile performance. Summary of the invention

[0007] In order to obtain a solder bar with good oxidation resistance, good spreadability and high tensile strength, the present application provides an anti-oxidation solder bar and a preparation method thereof.

[0008] In the first aspect, the present application provides an anti-oxidation solder bar adopting the following technical solution: An anti-oxidation solder bar comprises a Sn-Ag-Cu alloy and other additives, wherein the weight proportion of Sn in the Sn-Ag-Cu alloy is 96.5-98.5%, the weight proportion of Ag is 1-1.5%, and the weight proportion of copper is 0.5-2%; the other additives include Bi, Ge, P and Sn-Be-Sb ternary alloy, wherein the doping amount of Bi is 0.01-0.05% of the Sn-Ag-Cu alloy , the doping amount of Ge is 0.01-0.06% of the Sn-Ag-Cu alloy, the doping amount of P is 0.05-0.1% of the Sn-Ag-Cu alloy, and the doping amount of Sn-Be-Sb ternary alloy is 1.2-1.8% of the Sn-Ag-Cu alloy. In the Sn-Be-Sb ternary alloy, the weight percentage of Be is 4.8-5.6%, the weight percentage of Sb is 2.5-3.8%, and Sn is the balance.

[0009] In the present application, the anti-oxidation solder bar is made of a specific ratio of Sn (tin) - Ag (silver) - Cu (copper) alloy, Bi (bismuth), Ge (germanium), P (phosphorus) and Sn (tin) - Be (beryllium) - Sb (antimony) ternary alloy, and the Sn-Be-Sb ternary alloy is made of a specific ratio of tin, beryllium and antimony. Different from the solder bar made of the traditional Sn-Ag-Cu alloy, the present application also adds Bi, Ge, P and Sn-Be-Sb ternary alloy. Through the joint action of the raw materials, the anti-oxidation performance of the solder bar can be improved, the formation of the oxide layer can be reduced, and the smoothness and aesthetics can be maintained; at the same time, an anti-oxidation solder bar with excellent fluidity, good spreadability, low temperature (180℃-200℃) welding and good welding effect and tensile strength can be obtained.

[0010] It should be noted that the ratio of each raw material plays a key role in obtaining the anti-oxidation solder bar with good oxidation resistance, good spreadability and high tensile strength in this application, and the ratio of each raw material should not exceed the above range of this application. In addition, compared with directly adding Be and Sb, adding Be and Sb in the form of Sn-Be-Sb ternary alloy can effectively improve the tensile strength and oxidation resistance of the anti-oxidation solder bar.

[0011] In some preferred embodiments, in the Sn-Ag-Cu alloy, the weight proportion of Sn is 97-97.5%, the weight proportion of Ag is 1-1.5%, and the weight proportion of copper is 1-2%.

[0012] In some preferred embodiments, the Bi doping amount is 0.03-0.05% of the Sn-Ag-Cu alloy, the Ge doping amount is 0.04-0.06% of the Sn-Ag-Cu alloy, the P doping amount is 0.05-0.06% of the Sn-Ag-Cu alloy, and the Sn-Be-Sb ternary alloy is 1.2-1.5% of the Sn-Ag-Cu alloy.

[0013] In some preferred embodiments, in the Sn—Be—Sb ternary alloy, the weight percentage of Be is 5.0-5.2%, the weight percentage of Sb is 2.8-3.2%, and Sn is the balance.

[0014] In the present application, the ratio of each raw material is preferably selected, and the weight percentage of Be in the Sn-Be-Sb ternary alloy is controlled to be 5.0-5.2%, the weight percentage of Sb is 2.8-3.2%, and Sn is the balance, which can further improve the spreading coefficient, antioxidant performance and tensile properties of the antioxidant solder bar, and is beneficial to improving the welding quality of the antioxidant solder bar.

[0015] In some specific embodiments, the method for preparing the Sn-Be-Sb ternary alloy comprises the following steps: S1. After Sn is melted at 240-250°C in an inert gas environment, the temperature is raised to 350-360°C, Sb and Be are added, and the mixture is stirred and melted uniformly to obtain a molten material; S2. pouring the molten material into a mold and cooling it to obtain a Sn-Be-Sb ternary alloy.

[0016] In some preferred embodiments, S1, Sn is melted at 240-250°C in an inert gas environment, the temperature is raised to 350-360°C, Sb and Be are added, stirred and melted uniformly, and then the temperature is lowered to 200-220°C and kept warm for 0.5-1h to obtain a molten material.

[0017] In the present application, when preparing the Sn-Be-Sb ternary alloy, adding the step of cooling to 200-220°C and keeping warm for 0.5-1h can further improve the spreading coefficient, antioxidant properties and tensile properties of the antioxidant solder bar, which is beneficial to improving the welding quality of the antioxidant solder bar.

[0018] In a second aspect, the present application provides a method for preparing an anti-oxidation solder bar using the following technical solution: A method for preparing an anti-oxidation solder bar comprises the following steps: 1. Put the Sn-Ag-Cu alloy into a vacuum melting furnace, and melt it evenly under the protection of nitrogen. Then add Bi, Ge, P and Sn-Be-Sb ternary alloy, continue to stir and melt evenly to obtain a molten liquid; 2. Casting and extruding the molten liquid to obtain an anti-oxidation solder bar.

[0019] In some preferred embodiments, in (1), the melting temperature is controlled to be 315-325°C.

[0020] In the present application, the melting temperature is controlled at 315-325° C., which is conducive to the uniform fusion of various raw materials and has a promoting effect on improving the welding performance of the anti-oxidation solder bar.

[0021] In summary, this application at least includes the following beneficial technical effects: (1) Different from the solder bar made of traditional Sn-Ag-Cu alloy, the present application also adds Bi, Ge, P and Sn-Be-Sb ternary alloy. Through the joint action of the raw materials, the anti-oxidation performance of the solder bar can be improved, the formation of the oxide layer can be reduced, and the smoothness and aesthetics can be maintained; at the same time, an anti-oxidation solder bar with excellent fluidity, good spreadability, low-temperature (180℃-200℃) welding and good welding effect and tensile strength can be obtained.

[0022] (2) In the present application, the ratio of each raw material is preferably selected, and the weight percentage of Be in the Sn-Be-Sb ternary alloy is controlled to be 5.0-5.2%, the weight percentage of Sb is 2.8-3.2%, and Sn is the balance, which can further improve the spreading coefficient, antioxidant performance and tensile properties of the antioxidant solder bar, and is beneficial to improving the welding quality of the antioxidant solder bar. DETAILED DESCRIPTION

[0023] The present application is further described below in conjunction with specific experiments. Example

[0024] [Example 1] An anti-oxidation solder bar comprises a Sn-Ag-Cu alloy and other additives, wherein the weight percentage of Sn is 96.5%, the weight percentage of Ag is 1.5%, and the weight percentage of copper is 2% in the Sn-Ag-Cu alloy; the other additives comprise Bi, Ge, P, and a Sn-Be-Sb ternary alloy, wherein the doping amount of Bi is 0.01% of the Sn-Ag-Cu alloy, the doping amount of Ge is 0.06% of the Sn-Ag-Cu alloy, the doping amount of P is 0.05% of the Sn-Ag-Cu alloy, the doping amount of the Sn-Be-Sb ternary alloy is 1.8% of the Sn-Ag-Cu alloy, and in the Sn-Be-Sb ternary alloy, the weight percentage of Be is 4.8%, the weight percentage of Sb is 3.8%, and the weight percentage of Sn is 91.4%. The preparation method of the Sn-Be-Sb ternary alloy comprises the following steps: S1. After 91.4 kg Sn is melted at 250 ° C in an inert gas environment, the temperature is raised to 350 ° C, 3.8 kg Sb and 4.8 kg Be are added, and the mixture is stirred and melted uniformly to obtain a molten material; S2. Pour the molten material into a mold and cool it to obtain a Sn-Be-Sb ternary alloy.

[0025] In this embodiment, the method for preparing the anti-oxidation solder bar comprises the following steps: (1) Putting the Sn-Ag-Cu alloy into a vacuum melting furnace, melting it uniformly at 315°C under nitrogen protection, then adding Bi, Ge, P and Sn-Be-Sb ternary alloy, and continuing to stir and melt it uniformly to obtain a molten liquid; (2) Casting and extruding the molten liquid to obtain an anti-oxidation solder bar.

[0026] [Example 2] An anti-oxidation solder bar comprises a Sn-Ag-Cu alloy and other additives, wherein the weight percentage of Sn is 98.5%, the weight percentage of Ag is 1%, and the weight percentage of copper is 0.5% in the Sn-Ag-Cu alloy; the other additives comprise Bi, Ge, P, and a Sn-Be-Sb ternary alloy, wherein the doping amount of Bi is 0.05% of the Sn-Ag-Cu alloy, the doping amount of Ge is 0.01% of the Sn-Ag-Cu alloy, the doping amount of P is 0.1% of the Sn-Ag-Cu alloy, the doping amount of the Sn-Be-Sb ternary alloy is 1.2% of the Sn-Ag-Cu alloy, and in the Sn-Be-Sb ternary alloy, the weight percentage of Be is 5.6%, the weight percentage of Sb is 2.5%, and the weight percentage of Sn is 91.9%. The preparation method of the Sn-Be-Sb ternary alloy comprises the following steps: S1. After 91.9 kg Sn is melted at 240 ° C in an inert gas environment, the temperature is raised to 360 ° C, 2.5 kg Sb and 5.6 kg Be are added, and the mixture is stirred and melted uniformly to obtain a molten material; S2. Pour the molten material into a mold and cool it to obtain a Sn-Be-Sb ternary alloy.

[0027] In this embodiment, the method for preparing the anti-oxidation solder bar comprises the following steps: (1) (1) Put the Sn-Ag-Cu alloy into a vacuum melting furnace, and melt it uniformly at 325°C under nitrogen protection, then add Bi, Ge, P and Sn-Be-Sb ternary alloy, continue to stir and melt uniformly, and obtain a molten liquid; (2) Casting and extruding the molten liquid to obtain an anti-oxidation solder bar.

[0028] [Example 3] An anti-oxidation solder bar comprises a Sn-Ag-Cu alloy and other additives, wherein the weight percentage of Sn is 97.2%, the weight percentage of Ag is 1.3%, and the weight percentage of copper is 1.5% in the Sn-Ag-Cu alloy; the other additives comprise Bi, Ge, P, and a Sn-Be-Sb ternary alloy, wherein the doping amount of Bi is 0.04% of the Sn-Ag-Cu alloy, the doping amount of Ge is 0.05% of the Sn-Ag-Cu alloy, the doping amount of P is 0.055% of the Sn-Ag-Cu alloy, the doping amount of the Sn-Be-Sb ternary alloy is 1.35% of the Sn-Ag-Cu alloy, and in the Sn-Be-Sb ternary alloy, the weight percentage of Be is 5.1%, the weight percentage of Sb is 3.0%, and the weight percentage of Sn is 91.9%.

[0029] In this embodiment, the preparation method of the Sn-Be-Sb ternary alloy and the preparation method of the anti-oxidation solder bar are consistent with [Example 1].

[0030] [Example 4] An anti-oxidation solder bar, which differs from [Example 3] in that the preparation method of the Sn-Be-Sb ternary alloy is different. In this embodiment, the preparation method of the Sn-Be-Sb ternary alloy includes the following steps: S1. After 91.9 kg Sn was melted at 250 ° C in an inert gas environment, the temperature was raised to 350 ° C, 3.0 kg Sb and 5.1 kg Be were added, stirred and melted uniformly, and then the temperature was lowered to 210 ° C and kept warm for 0.5 h to obtain a molten material; S2. Pour the molten material into a mold and cool it to obtain a Sn-Be-Sb ternary alloy.

[0031] Comparative Example [Comparative Example 1] A solder bar, which differs from [Example 1] in that: no Sn-Be-Sb ternary alloy is added, but equal contents of Sn, Be and Sb are added respectively.

[0032] [Comparative Example 2] A solder bar, which differs from [Example 1] in that P is not added.

[0033] [Comparative Example 3] A solder bar, which differs from [Example 1] in that Bi and Ge are not added.

[0034] Performance testing (1) Spreading coefficient: The spreading coefficient of the solder bars prepared in each embodiment and comparative example was tested with reference to GB / T 11364-89 "Test method for spreadability and seam filling property of solder". The spreading substrate was a 0.2 mm thick pure copper sheet, the test temperature was 400°C, and the test time was 10 s. The larger the spreading coefficient, the better the wettability of the solder bar, which is beneficial to improving the welding strength of the solder bar.

[0035] (2) Antioxidation: The solder bars prepared in the examples and comparative examples were melted at 250°C, 400°C and 550°C and kept warm for 24 hours. The oxide film on the surface of the liquid solder was scraped off and the weight of the oxide film was weighed after cooling to room temperature. In each test, the test weight of the solder bar was 100g. The less the oxide film, the better the antioxidation property of the solder bar.

[0036] (3) Tensile strength: The tensile strength of the solder bars prepared in each embodiment and comparative example was tested with reference to GB / T 228.1-2021 “Tensile test of metallic materials - Part 1: Room temperature test method”. The greater the tensile strength, the more conducive it is to improving the stability of the welded joint.

[0037] Table 1 Combining the above-mentioned Example 1 with Comparative Examples 1-3 and the test data in Table 1, it can be seen that the Sn-Be-Sb ternary alloy, P, Bi and Ge all play a key role in improving the oxidation resistance of the solder bar. In addition, the addition of the Sn-Be-Sb ternary alloy can further improve the tensile strength of the solder bar, which is beneficial to improving the stability of the welded joint.

[0038] Combining the above-mentioned Example 1 and Example 3 and the test data in Table 1, it can be seen that by optimizing the ratio of each raw material, the spreading coefficient, antioxidant performance and tensile performance of the anti-oxidation solder bar can be further improved, which is beneficial to improving the welding quality of the anti-oxidation solder bar.

[0039] Combining the above-mentioned Example 3 and Example 4 and the test data in Table 1, it can be seen that by further optimizing the preparation method of the Sn-Be-Sb ternary alloy, the oxidation resistance and tensile properties of the antioxidant solder bar can be further improved, which is beneficial to further improve the welding quality of the antioxidant solder bar.

[0040] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An anti-oxidation solder bar, characterized in that: It comprises a Sn-Ag-Cu alloy and other additives, wherein the weight percentage of Sn in the Sn-Ag-Cu alloy is 96.5-98.5%, the weight percentage of Ag is 1-1.5%, and the weight percentage of copper is 0.5-2%; the other additives comprise Bi, Ge, P and a Sn-Be-Sb ternary alloy, wherein the doping amount of Bi is 0.01-0.05% of the Sn-Ag-Cu alloy, the doping amount of Ge is 0.01-0.06% of the Sn-Ag-Cu alloy, the doping amount of P is 0.05-0.1% of the Sn-Ag-Cu alloy, the doping amount of the Sn-Be-Sb ternary alloy is 1.2-1.8% of the Sn-Ag-Cu alloy, and in the Sn-Be-Sb ternary alloy, the weight percentage of Be is 4.8-5.6%, the weight percentage of Sb is 2.5-3.8%, and Sn is the balance.

2. The anti-oxidation solder bar according to claim 1, characterized in that: In the Sn-Ag-Cu alloy, the weight proportion of Sn is 97-97.5%, the weight proportion of Ag is 1-1.5%, and the weight proportion of copper is 1-2%.

3. The anti-oxidation solder bar according to claim 1, characterized in that: The doping amount of Bi is 0.03-0.05% of the Sn-Ag-Cu alloy, the doping amount of Ge is 0.04-0.06% of the Sn-Ag-Cu alloy, the doping amount of P is 0.05-0.06% of the Sn-Ag-Cu alloy, and the doping amount of the Sn-Be-Sb ternary alloy is 1.2-1.5% of the Sn-Ag-Cu alloy.

4. The anti-oxidation solder bar according to claim 1, characterized in that: In the Sn-Be-Sb ternary alloy, the weight percentage of Be is 5.0-5.2%, the weight percentage of Sb is 2.8-3.2%, and Sn is the balance.

5. The anti-oxidation solder bar according to claim 1, characterized in that: The preparation method of the Sn-Be-Sb ternary alloy comprises the following steps: S1. After Sn is melted at 240-250°C in an inert gas environment, the temperature is raised to 350-360°C, Sb and Be are added, and the mixture is stirred and melted uniformly to obtain a molten material; S2. pouring the molten material into a mold and cooling it to obtain a Sn-Be-Sb ternary alloy.

6. The anti-oxidation solder bar according to claim 5, characterized in that: S1. After Sn is melted at 240-250°C in an inert gas environment, the temperature is raised to 350-360°C, Sb and Be are added, stirred and melted evenly, and then the temperature is lowered to 200-220°C and kept warm for 0.5-1h to obtain a molten material.

7. A method for preparing an anti-oxidation solder bar as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Put the Sn-Ag-Cu alloy into a vacuum melting furnace and melt it evenly under the protection of nitrogen. Then add Bi, Ge, P and Sn-Be-Sb ternary alloy and continue to stir and melt them evenly to obtain a molten liquid. (2) The molten liquid is cast and extruded to obtain an anti-oxidation solder bar.

8. The method for preparing an anti-oxidation solder bar according to claim 7, characterized in that: (1), the melting temperature is controlled at 315-325°C.

Citation Information

Patent Citations

  • Antioxidant suitable for SnAgCu or SnCu solder and preparation method thereof

    CN105149809A

  • Antioxidant soldering tin bar

    CN105252164A

  • SnAgSbNi-based lead-free solder alloy as well as preparation method and application thereof

    CN106825983A

  • SnSbNi series high-melting-point antioxidant lead-free soldering tin alloy and preparation method and application thereof.

    CN108715949A

  • Leadless alloy for soldering flux

    CN1195592A